The Influence of Financial Literacy and Income on the Decision to Invest in Islamic Stocks - Galang Kalifat Ekanagara; Novi Puspitasari; Akhmad Munir (Optima Science, 2023)
The capital market plays a significant role in a country's economy as a meeting place between those in need of capital and those who have capital for investment. However, good financial literacy and income factors influence investment decisions. Data shows an increase in the number of investors in the capital market, but low levels of financial literacy, particularly among young investors, remain a challenge. This research utilizes the Planned Behavior Theory (PBT) to understand the factors that influence investment decisions, while also highlighting the growing interest in Shariah-based investments. For students, financial literacy and income have a significant impact on their investment decisions. The research findings indicate that improving financial literacy and income management can assist individuals in making better investment decisions and enhancing their financial well-being.